PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, WHISTLEBLOWING SYSTEM, DAN BYSTANDER EFFECT TERHADAP KECENDERUNGAN KECURANGAN DALAM PENGELOLAAN DANA BUMDES (Studi Empiris Pada Badan Usaha Milik Desa Di Kabupaten Klungkung): (Studi Empiris pada Badan Usaha Milik Desa di Kabupaten Klungkung) - Putu Gede Suwidia Putra Adnyana; I Putu Gede Diatmika (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
This study aims to determine the effect of human resources, the violation reporting system, and the effect of observers on fraud in the management of BUMDes funds. This type of research is quantitative research. This study uses primary data obtained by questionnaire with a population of all BUMDes recorded in the Klungkung Regency government, including 48 types of BUMDes. The sample of this research is 28 units of BUMDes. This sample was determined by purposive sampling method. The respondents of this study consisted of the chairman, secretary, treasurer and members. The independent variables used in this study are human resources, whistleblowing system, and the bystander effect. The results showed (1) human resources had a negative effect on the tendency of fraud in the management of BUMDes funds, (2) the reporting system of violations negatively affected the tendency of fraud in the management of BUMDes funds, (3) the influence of observers had a positive effect on the tendency of fraud in the management of BUMDes funds.